Hammer Grain Crushers: Classification and Efficiency Assessment - Artem A. Mezenov; Nikolai N. Grigorev; Nikolai I. Kashevarov (Техника и технология пищевых производств)
Grain milling is one of the most complex and energy-consuming procedures in the technology of concentrated mixed fodders. Unfortunately, manufacturers provide hammer grain crushers only with technical characteristics, supplying neither technological nor economic performance indicators, which makes it difficult for consumers to select the optimal machine. The article introduces a classification of hammer grain crushers and a methodology for assessing their energy efficiency. The design, technical, and economic indicators of agricultural hammer crushers were obtained by calculation and analysis of specific metal intensity and energy consumption. The data pool consisted of technical and economic indicators of domestic and foreign hammer crushers, divided into mechanical and pneumatic ones by the type of loading. The classification relied on the following properties: the type of design, working chamber, feeding, removal, and orientation of the rotor shaft; the presence or absence of grates and decks; the number of stages and discs. The classification was structured as a table of technical and economic indicators for different types and brands. The authors introduced a complex performance index to assess the efficiency of pneumatic and mechanical grain crushers. It took into account the metal consumption and energy consumption. For pneumatic and mechanical hammer crushers with a productivity of ≤ 1, 1–3, 3–5, 5–10, and ≥ 10 t, the index varied from 0.1 to 2.22 (kWt/h/tm)/t: the more efficient the crusher, the lower the index value. The complex performance index and its graphical representation simplify the selection procedure for the consumer. The results obtained demonstrate the improvement prospects for hammer crushers design.